VEGFR2-targeted antibody fused with IFNαmut regulates the tumor microenvironment of colorectal cancer and exhibits potent anti-tumor and anti-metastasis activity - Pengzhao Shang; Rui Gao; Yijia Zhu; Xiaorui Zhang; Yang Wang; Minji Guo; Hui Peng; Min Wang; Juan Zhang (Elsevier, 2021)
Although interferon α (IFNα) and anti-angiogenesis antibodies have shown appropriate clinical benefit in the treatment of malignant cancer, they are deficient in clinical applications. Previously, we described an anti-vascular endothelial growth factor receptor 2 (VEGFR2)-IFNα fusion protein named JZA01, which showed increased in vivo half-life and reduced side effects compared with IFNα, and it was more effective than the anti-VEGFR2 antibody against tumors. However, the affinity of the IFNα component of the fusion protein for its receptor-IFNAR1 was decreased. To address this problem, an IFNα-mutant fused with anti-VEGFR2 was designed to produce anti-VEGFR2-IFNαmut, which was used to target VEGFR2 with enhanced anti-tumor and anti-metastasis efficacy. Anti-VEGFR2-IFNαmut specifically inhibited proliferation of tumor cells and promoted apoptosis. In addition, anti-VEGFR2-IFNαmut inhibited migration of colorectal cancer cells and invasion by regulating the PI3K-AKT-GSK3β-snail signal pathway. Anti-VEGFR2-IFNαmut showed superior anti-tumor efficacy with improved tumor microenvironment (TME) by enhancing dendritic cell maturation, dendritic cell activity, and increasing tumor-infiltrating CD8+ T cells. Thus, this study provides a novel approach for the treatment of metastatic colorectal cancer, and this design may become a new approach to cancer immunotherapy.